A structural study of dithizone coordination chemistry - Rice, Craig R.; Faulkner, Robert A.; Jewsbury, Roger A.; Bullock, Samantha; Dunmore, Rachel (CrystEngComm, 2017)
Dithizone, since its discovery in 1878, has become essential in colorimetric assays for numerous transition metal ions. However, despite it being a vital reagent its coordination chemistry is not fully understood. Here we give insight into the binary complexes of dithizone, which contain two different metal ions, and the secondary complexes with Cu(ii) which can either involve reduction of the metal ion or double deprotonation of dithizone giving the self-assembled [(H-DPTC)8Cu8] and [(DPTC)4Cu4] species respectively.